Gametas como mercadorias: a superação dos desafios ético-jurídicos da comodificação de gametas humanos - Lucas Costa de Oliveira (2021)
This thesis is based on the problem of the commodification of human gametes. Thus, its first objective is to highlight the various practices that, to a greater or lesser extent, involve the commodification of gametes: import and export of gametes from the United States, egg sharing, compensation models without precise criteria, parallel practices, such as home insemination and transactions through social networks, as well as the black market. From this context, the hypothesis arises that gametes can and should be understood as objects of property, submitted to a regulated market based on ethical criteria, unless it hinders the free development of the personhood or violates the most important values of a given community. To verify the correctness of the hypothesis presented, three chapters are covered. In the first, the alleged ban on the sale of gametes under Brazilian law is investigated, arguing that there is no express prohibition in this regard. Nevertheless, there is a legislative tendency to prohibit commercial transactions in any part of the human body. Thus, the most direct norm that addresses the theme, refers to the constitutional prohibition of commercialization of human "substances", which can be relativized from an analytical methodology that questions both the scope of the term itself and the practices that are inserted in the normative scope, especially from recent decisions of the Brazilian Supreme Federal Court. The second chapter seeks to identify what would be the most appropriate way to categorize human gametes, based on two hypotheses: personality rights and property rights. After demonstrating the inconsistencies of personality rights, it is argued that the property rights would be more appropriate to protect detached parts of the human body, since its dogmatic and functional structure allows adaptation to different contexts and objects, while guaranteeing a prima facie theoretical-conceptual framework to deal with the new and complex problems arising from the radical possibility of manipulating the human body and its detached parts. Finally, the third chapter seeks to present several theories of commodification so that parameters can be established to assess the (in)correction of gamete commercialization. The theory of incomplete commodification is adopted as a theoretical framework, since it admits the possibility of the coexistence of a plurality of conflicting values ​​over the same social good, also defending the possibility of regulated markets for contested commodities. In the end, in order to bring clarity to the argument, it is analysed the main objections to the commodification of human gametes: solidarity, justice, exploitation, coercion, harm and objectification. After analysing each of these arguments, it is concluded that gametes can be commercialized under a regulated market that takes into account the parameters of justice presented, in such a way that there are no ethical reasons strong enough to justify the total ban on the commodification of gametes – except for the public-political consensus, which, in an ultimate analysis, defines the type of society that a community intends to reach.